Design and fabricate multipurpose trolley - Al Nazirul, Haron (2010)
Trolley is the main transport for human to carry load. Every trolley has different use and specific use. It is limited to do other job than the specified job. There are some disadvantages for common trolleys such as don’t have stopper,load easy to fall due to slippery surface only suitable for flat road, hard to cornering, cannot load many things, unstable for heavy duty work, high force needed to push or pull the trolley. To reduce this problem, one new trolley will be development that have multipurpose and has not limited to do another task or job. Nowadays, people use trolley to carry heavy load. There are many type of trolley in the market like industrial trolley, drum truck trolley and platform truck trolley.Many trolleys has been developed with a specific task or job like shopping trolley whichcan be use only for shopping, and transporting traytrolley only to carry trays. In the fabrication, there are many process involve to develop the product such as grinding, joining, measuring, gathering material, cutting material, and finishing process.This project is about design and fabricates a new product of trolley that has multi function. The trolley maximum loads must 200kg, multi use and easy assemble. Its also must reduce the disadvantages of the trolley in the current market like have stopper, and able to lift items up the stairs. Trolley was achieving the objective of this project. The Multipurpose Trolley can function in good condition for example it can support 200 kg load and the Trolley can climb the upstairs.